Hubungan kejadian dispepsia dengan kebutuhan istirahat tidur pada mahasiswa S1 keperawatan - Ridha Ghina Nurjanah; Ahmad Purnama Hudayana; Ria Inriyana (Holistik Jurnal Kesehatan, 2024)
Background: Functional Dyspepsia is a group of symptoms in the upper digestive tract which are characterized by pain or discomfort in the pit of the stomach, stomach feeling bloated, feeling full quickly, and nausea and vomiting without any organic abnormalities and generally occurs in the productive age. Symptoms of dyspepsia will get worse if not treated quickly, such as avoiding the factors that cause it. Bad lifestyle factors are the biggest contributor to the incidence of dyspepsia, one of which is the lack of need for sleep rest. Purpose: To determine the relationship between the need for sleep rest and the incidence of dyspepsia in undergraduate nursing students. Method: Quantitative descriptive research with a cross sectional approach. The sampling technique is total sampling with a sample size of 153 respondents. Data collection uses PADYQ and PSQI instruments. The statistical analysis test in this research used descriptive and Pearson correlation (p<0.05). Results: Shows that there is a significant relationship between the need for sleep rest and the incidence of dyspepsia (p-value = 0.000), obtained a positive value or in the same direction (r = 0.396). Conclusion: The need for poor sleep rest greatly influences the increase in dyspepsia symptoms. Suggestion: Students can carry out self-management to fulfill the need for good sleep rest by paying attention to various factors that trigger and prevent it, such as managing good sleep duration, managing sleep patterns, comfort while sleeping, and managing lifestyle patterns.   Keywords: Dyspepsia; Nursing; Sleep Rest.   Pendahuluan: Dispepsia Fungsional merupakan sekumpulan gejala pada saluran pencernaan atas yang ditandai dengan adanya rasa nyeri atau tidak nyaman pada ulu hati, perut terasa kembung, cepat kenyang, serta mual muntah tanpa adanya kelainan organik dan umumnya terjadi pada usia produktif. Gejala dispepsia akan semakin buruk jika tidak ditangani dengan cepat seperti menghindari faktor-faktor penyebabnya. Faktor gaya hidup yang buruk penyumbang terbesar kejadian dispepsia, salah satunya adalah kurangnya kebutuhan istirahat tidur. Tujuan: Untuk mengetahui hubungan kebutuhan istirahat tidur dengan kejadian dispepsia pada mahasiswa S1 Keperawatan. Metode: Penelitian deskriptif kuantitatif dengan pendekatan cross sectional. Teknik pengambilan sampel yaitu total sampling dengan jumlah sampel 153 responden. Pengumpulan data menggunakan instrumen yang PADYQ dan PSQI. Uji analisis statistik dalam penelitian ini menggunakan deskriptif dan pearson correlation (p<0.05). Hasil: Menunjukkan terdapat hubungan yang signifikan antara kebutuhan istirahat tidur dengan kejadian dispepsia (p-value = 0.000), didapatkan nilai positif atau searah (r = 0.396). Simpulan: Kebutuhan istirahat tidur yang buruk sangat berpengaruh terhadap peningkatan gejala dispepsia. Saran: Mahasiswa dapat melakukan self management untuk pemenuhan kebutuhan istirahat tidur yang baik dengan memperhatikan berbagai faktor pencetus dan pencegahannya seperti pengaturan durasi tidur yang baik, pengelolaan pola tidur, kenyamanan saat tidur, dan pengaturan pola gaya hidup.   Kata Kunci: Dispepsia; Istirahat Tidur; Keperawatan.